UJI BEBERAPA ISOLAT JAMUR ENDOFIT TERHADAP JAMUR TULAR BENIH DAN PERTUMBUHAN BIBIT CABAI MERAH - Nurhafida Nurhafida; Fifi Puspita (Jurnal Agroteknologi, 2022)
The aim of this study was to test several endophytic fungi isolates with high antagonistic power against seed borne fungi in vitro and their effect on the growth of chili (Capsicum annuum L.) seedlings in vivo. This research was conducted at the Plant Disease Laboratory and Greenhouse Faculty of Agriculture, Riau University from October 2018 to February 2019. This research was conducted experimentally using a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatment of endophytic fungi was applied using the seed immersion method. The results showed that giving the endophytic fungi Rhizictonia sp., Cephaloporium sp., T. virens from oil palm roots and T. virens from oil palm stems were able to suppress the incidence of seed-borne pathogenic fungi Fusarium sp., Colletotrichum sp. and Aspergillus sp.. Provision of endophytic fungus T. virens from oil palm roots can increase seed germination capacity by 14%, number of live seeds by 17% and increase seedling height and leaf number.